Comparative Analysis of Carbon, Ecological, and Water Footprints of Polypropylene-Based Composites Filled with Cotton, Jute and Kenaf Fibers - Jerzy Korol (Materials, 2020)
Composites containing natural fibers are considered environmentally friendly materials which is related to the reduced use of fossil fuels and the emission of carbon dioxide compared to petroleum-based polymers. Nevertheless, a complete evaluation of their environmental impact requires a broader view. This paper presents a carbon, ecological, and water footprints assessment of polypropylene-based composites filled with cotton, jute, and kenaf fibers based on a standardized European pallet (EUR-pallet) case study. Obtained results were compared with unmodified polypropylene and composite with glass fibers. Incorporation of 30 wt% of cotton, jute, and kenaf fibers into a polypropylene matrix reduced its carbon footprint by 3%, 18%, and 18%, respectively. Regarding the ecological footprint, an 8.2% and 9.4% reduction for jute and kenaf fibers were noted, while for cotton fibers, its value increased by 52%. For these footprints, the use of jute and kenaf fibers was more beneficial than glass fibers. Nevertheless, the application of natural fibers caused a 286%, 758%, and 891% drastic increase of water footprint of the final product, which was mainly affected by cultivation and irrigation of crops. Therefore, in a holistic view, the incorporation of natural fibers into the polypropylene matrix definitely cannot be impartially considered as an environmentally friendly solution.